Acute effect of alcohol on working memory updating. (3rd May 2021) - Cofresí, Roberto U.; Watts, Ashley L.; Martins, Jorge S.; Wood, Phillip K.; Sher, Kenneth J.; Cowan, Nelson; Miyake, Akira; Bartholow, Bruce D.
Abstract: Aims: To examine the acute effects of alcohol on working memory (WM) updating, including potential variation across the ascending limb (AL) and descending limb (DL) of the blood alcohol concentration (BAC) time‐course. Design: A two‐session experiment in which participants were randomly assigned to one of three beverage conditions [alcohol (males: 0.80 g/kg; females: 0.72 g/kg), active placebo (0.04 g/kg) or non‐alcohol control (tonic)] and one of two BAC limb testing conditions (AL and DL or DL‐only) for the second session, yielding a 3 (beverage) × 2 (time‐points tested) × 3 (time‐point) mixed factorial design with repeated measures on the latter factor. One of the repeated assessments is 'missing by design' in the DL‐only condition. Setting: A psychology laboratory at the University of Missouri campus in Columbia, MO, USA. Participants: Two hundred thirty‐one community‐dwelling young adults (51% female; aged 21–34 years) recruited from Columbia, MO, USA, tested between 2011 and 2013. Measurements: Latent WM updating performance as indexed by shared variance in accuracy on three WM updating tasks (letter memory, keep track, spatial 2‐back) at three time‐points. Findings: Multi‐group modeling of latent WM updating indicated that performance among participants who consumed placebo or control beverages improved during the second session at time‐points corresponding to AL (∆ from baseline in latent mean ± standard error (SE) + 0.5 ± 0.01, P < 0.001) and DL (+ 0.08 ± 0.01, P < 0.001). Alcohol consumption did not impair WM updating (∆ from baseline in latent mean ± SE, at AL: + 0.01 ± 0.01, P = 0.56; at DL: + 0.05 ± 0.01, P < 0.001), but attenuated performance improvements (equality of latent means across beverage groups at AL or DL: Δχ 2 (1) ≥ 7.53, P < 0.01). Conclusions: Acute alcohol‐induced impairment in working memory updating may be limited, but dampening of practice effects by alcohol could interfere with the completion of novel, unpracticed tasks.